Presentation slides - Stakeholders' Consultation Meeting on Agrifood value chains in Odisha Challenges and Opportunities - Mitra, Archisman; Ashok, K. R.; Pattnayak, Pravu Kalyan; Mishra, Dharitri; Dutta, Debjyoti; Kadian, M.S.; Mishra, Kamalesh; Biswal, Debadutta; Mishra, Nrusingha Charan; Barik, Nagesh Kumar; Bahta, Sirak T.; Nandi, Ekadashi (CGIAR Initiative on National Policies and Strategies, 2023)
These slides were used during the Stakeholders’ Consultation Meeting on Agrifood value chains in Odisha Challenges and Opportunities, at Auditorium, Department of Agriculture & Farmers' Empowerment (Krushi Bhavan) Bhubaneswar, Odisha, India on 29 November 2023.